Application of Situational Leadership Theory in Islamic Educational Institutions - Septia Irnanda Saputra; Hermen Irawadi; Asmendri; Milya Sari (International Journal of Technology and Education Research, 2025)
The purpose of this writing is toApplication of Situational Leadership Theory in Islamic Educational Institutionsknowing Situational leadership can affect teacher and employee performance. leadership is a process to be able to lead. Leaders must do something. leaders must tell teachers and employees to take action. Leaders tell teachers in various ways, such as using legitimate authority, creating models (setting examples). implementing situational leadership styles has met four indicators. This is evidenced by the results of the study that: First, the head of the madrasah has implemented the Telling style as evidenced by 1) giving work to teachers always giving orders, and not being coercive; 2) providing direction before carrying out the work. Second, the head of the madrasah has implemented the Selling style as evidenced by 1) making clear rules; 2) giving teachers the opportunity to express their opinions; 3) the head of the madrasah applies democracy; 4) can accept suggestions from teachers; 5) providing motivation to subordinates in completing work; 6) giving praise and incentives to teachers if they complete the work well. Third, the head of the madrasah has implemented the Participating style as evidenced by: 1) the head of the madrasah is able to make decisions appropriately in completing work; 2) the head of the madrasah is active in various activities carried out by the community. Fourth, the head of the madrasah has implemented a Delegating style, which is proven through: 1) the head of the madrasah monitors the work of teachers; 2) the head of the madrasah gives full responsibility to teachers in completing work.